Online versus Offline Entrepreneur Personalities: A Review on Entrepreneur Performance - Nor Asiah Yaakub , Khalil Md Nor , Noriza Mohd Jamal (International Journal of Advanced Science and Technology, 2020)
To date, entrepreneurs seem to dominate the establishment of business types. The success of asmall-scaled business relies heavily on the owner’s characteristics, such as their personality.Although vast studies have investigated entrepreneur personality as a success factor in an offlinesetting, only a handful have looked into the context of online. It is highly probable that a variableor perhaps more from the offline entrepreneur context is (are) missing within the onlineentrepreneur context. Additionally, new variables are yet to be unraveled in light of onlineentrepreneurs. The outcomes retrieved from a systematic literature review appear to support thisnotion. Hence, this study proposes a conceptual framework for online entrepreneur success byemphasizing personality variables. This calls for more empirical testing on the suggestedvariables in the context of online entrepreneurs shortly.